2020
DOI: 10.1007/s10751-020-01708-0
|View full text |Cite
|
Sign up to set email alerts
|

Simulation studies of the laser ablation ion source at the SHIPTRAP setup

Abstract: A gas-filled miniature Radio-Frequency Quadrupole (mini-RFQ) was recently implemented into the SHIPTRAP laser ablation ion source to thermalize the laser-ablated ions and thus improve production efficiency as well as sample preparation. This source provides reference ions of various elements for online experiments with the SHIPTRAP mass spectrometer. In addition, it can be used to provide long-lived rare and radioactive isotopes available only in small sample sizes for high-precision mass measurements or to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Such a configuration anticipates that it will be possible to form an unbalanced 48 Ca + -40 Ca + ion crystal prior to the 232 Th + -40 Ca + one, to carry out a proof of principle experiment. A mini radiofrequency quadrupole (RFQ) structure [43] built by the group of Michael Block, is currently under commissioning in the beamline to produce and inject 232 Th + ions in the Penning trap. Besides thorium ions, the mini-RFQ will allow injecting other ion species produced from metallic samples by laser ablation (for laser ablation see, e.g., [44]).…”
mentioning
confidence: 99%
“…Such a configuration anticipates that it will be possible to form an unbalanced 48 Ca + -40 Ca + ion crystal prior to the 232 Th + -40 Ca + one, to carry out a proof of principle experiment. A mini radiofrequency quadrupole (RFQ) structure [43] built by the group of Michael Block, is currently under commissioning in the beamline to produce and inject 232 Th + ions in the Penning trap. Besides thorium ions, the mini-RFQ will allow injecting other ion species produced from metallic samples by laser ablation (for laser ablation see, e.g., [44]).…”
mentioning
confidence: 99%
“…In order to increase the sensitivity for offline experiments on rare isotopes, simulation studies of the laser-ablation ion source were performed and details can be found in Ref. [65].…”
Section: The Reference-ion Sourcesmentioning
confidence: 99%